The Effect of ginger herbal spray on reducing xerostomia in patients with type II diabetes - Homeira Mardani; Alireza Ghannadi; Bahareh Rashnavadi; Razieh Kamali (Mashhad University of Medical Sciences, 2017)
Objective: The aim of the present study is to evaluate the effect of ginger herbal spray on reducing dry mouth in patients with Type II diabetes. Materials and Method:This clinical trial was conducted on 20 patients with Type II diabetes suffering from dry mouth. The control individual for each patient was the same patient himself/herself. Each patient filled out his/her questionnaire at three different times, (before treatment, after treatment with placebo, and after taking the drug). Furthermore, the Schirmer test was performed to measure the flow of saliva in the patients. The drug and the placebo were prepared as oral sprays containing herbal extracts of ginger. Results:The mean amount of saliva after using the ginger plant spray increased significantly (p